ANALISIS DAMPAK LINGKUNGAN TERHADAP KEGIATAN OBJEK WISATA TAMAN PURBAKALA KERAJAAN SRIWIJAYA KOTA PALEMBANG - Halimzikri, Muhammad Abimas; Bochori; Nugrasyah, Amrillah; Islami, Fajar Sadik (LATERAL: Jurnal Teknik Sipil, 2025)
Tourist attractions have an important role in the economic development of a region, but can also cause negative impacts such as environmental pollution due to operational activities of tourist attractions that invite many visitors which can produce waste. The purpose of this paper is to identify and analyze the environmental impacts that occur due to operational activities of the Sriwijaya Kingdom Archaeological Park in Palembang City. The research method used is survey and observation as well as sampling of ambient water and air quality which will later be analyzed by an accredited laboratory. Furthermore, the data analysis carried out is in the form of descriptive data analysis. The results of testing air and surface water quality samples showed that all parameters tested did not exceed the established environmental quality standards, and the noise level also did not exceed the threshold. For the magnitude of traffic congestion, a V/C value of 0.31 was obtained, which indicates that the traffic flow generated from this activity is a stable flow. Thus, the operational activities of the Sriwijaya Kingdom Archaeological Park tourist attraction do not affect environmental quality, but it is necessary to monitor the water quality around the location of the activity.